PERANCANGAN VIDEO PROMOSI UNIVERSITAS ADZKIA DI KOTA PADANG - Hanafi Malik; Muhamad Ilham; Ramadhi, Ramadhi; Eko Fikriando (Asosiasi Dosen Muda Indonesia, 2024)
Video production is a stage that requires attention to detail and creativity. The use of appropriate equipment, good lighting, and capturing images from various engaging angles can enhance the visual quality of the video. The aim of this research is to identify the key elements that should be included in a promotional video for Universitas Adzkia to effectively attract prospective students in Padang City. The method used in this research is descriptive qualitative. The findings indicate that the promotional video for Universitas Adzkia already demonstrates many positive elements, but some adjustments in format, style, duration, quality, and distribution strategy are necessary to achieve higher effectiveness and optimally attract prospective students.